A tecnologia como ferramenta de ensino em sala de aula na disciplina de língua inglesa: percursos de desenvolvimento docente - Knorst, Lilian Birk (Universidade do Vale do Rio dos Sinos, 2019)
Thinking about teacher education, in the context of continuing education, implies thinking about formats that develop knowledge from different fields (TARDIF, 2002). In the field of technology in education, it is no different. It is important to think not only about the knowledge about technology, but also about how to use technology in the classroom, but about the teacher's relationship with the technologies in education, and the teacher's role in relation to these knowledge (CARNIN, 2016). For different formats, different competences are fostered because they come from different fields of knowledge. It is in this context that the present work is inserted, trying to understand how teachers in formation are related pedagogically with the use of technologies in education, in order to promote a discussion about principles that can be used to construct a proposal of an effective continuous formation. In addition, it is known that spaces of continuous formation are not lacking. In methodological terms, the researcher, based on the principles of a qualitative research (DIAS, 2000), observed an event of continuous formation of a group of teachers of English Language, belonging to a municipal network of basic education of Vale dos Sinos. From this observation, a field diary was created, which encouraged the elaboration of a questionnaire sent to all participating teachers and a semi-structured interview with a teacher of the group. The interview was recorded, transcribed and analyzed. The data show that continuing training, focused on learning about the use of technologies in the classroom, is a space of articulation between the four knowledges (TARDIF, 2002), without privileging only one. Thus, the proposition and organization of any continuing training course should consider the understanding of teaching English Language of the teaching staff, and ensure spaces for the teacher to bring their needs, re-signify their knowledge, share lesson plans and receive "feedback" in the course.
Keywords: Formação continuada; Tecnologias na educação; Relação professor-tecnologias; Continuing education; Technologies in education; Teacher-technology relation